A New Stage in the Development of Military Education in the Republic of Uzbekistan - Davranov Abdullah (Peerian Journals Publishing, 2022)
This article talks about the new stage of the development of military education in the Republic of Uzbekistan. Based on military data, the author analyzed the problem based on the existing scientific literature and studied the specific aspects of the new stage of military education development in the Republic of Uzbekistan.
Keywords: Uzbekistan; military training; Armed Forces; development